2011
DOI: 10.1016/j.cllc.2011.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Prognostic Value of Soluble Epidermal Growth Factor Receptor Plasma Concentration in Advanced Non–Small-Cell Lung Cancer Patients

Abstract: Low baseline sEGFR is associated with reduced survival in advanced NSCLC. Therefore, our findings in this large cohort of patients suggest that the determination of sEGFR concentration provides valuable prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
2
21
1
1
Order By: Relevance
“…Despite some reports showing increased values in affected patients, [36][37][38] most studies (and those including a higher number of subjects) reported a decrease of serum EGFR in cancer patients, with a proportional impact on survival. 18,[39][40][41][42][43][44] This supports the hypothesis that serum EGFR could be a different isoform with a physiological and tumorprotective role in the control of the EGFR-regulated signaling. 34 Similarly, we observed a reduction of serum EGFR in OSCC patients, but it was not possible to recognize any important impact on survival.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Despite some reports showing increased values in affected patients, [36][37][38] most studies (and those including a higher number of subjects) reported a decrease of serum EGFR in cancer patients, with a proportional impact on survival. 18,[39][40][41][42][43][44] This supports the hypothesis that serum EGFR could be a different isoform with a physiological and tumorprotective role in the control of the EGFR-regulated signaling. 34 Similarly, we observed a reduction of serum EGFR in OSCC patients, but it was not possible to recognize any important impact on survival.…”
Section: Discussionsupporting
confidence: 77%
“…In the international literature, several studies have evaluated the diagnostic potential of serum EGFR in other tumors (in particular breast, lung, and ovarian tumors) with conflicting results. Despite some reports showing increased values in affected patients, most studies (and those including a higher number of subjects) reported a decrease of serum EGFR in cancer patients, with a proportional impact on survival . This supports the hypothesis that serum EGFR could be a different isoform with a physiological and tumor‐protective role in the control of the EGFR‐regulated signaling .…”
Section: Discussionmentioning
confidence: 69%
“…These results are extremely interesting even though somewhat puzzling. Recent publications support the concept that circulating sEGFR tend to decrease in patients with neoplastic lesions [17,24,25], however larger clinical cohorts and experimental studies are needed to consolidate this observation and to clarify the role of the sEGFR in the circulation. The albumin/IgG-depleted plasma samples (500 l) analyzed in panel a were immunoprecipitated using the anti-EGFR(NT2) antibody and fractionated using OFFGEL and immunoblotted with the anti-EGFR(NT1) antibody.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, clinical data regarding the potential of sEGFR as a prognostic biomarker in patients with various solid tumours remain controversial. Lower sEGFR levels were associated with reduced survival in advanced NSCLC patients [47] and in meningioma [12]. In agreement with an antiproliferative function, sEGFRs were reported to inhibit tumour cell proliferation and migration in NSCLC cell lines [48].…”
Section: Splicing Of Egfr: An Alternative Methods To Control Tumourmentioning
confidence: 98%